2002
DOI: 10.1161/01.cir.0000039288.86470.dd
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Antagonist Lacidipine Slows Down Progression of Asymptomatic Carotid Atherosclerosis

Abstract: The greater efficacy of lacidipine on carotid IMT progression and number of plaques per patient, despite a smaller ambulatory blood pressure reduction, indicates an antiatherosclerotic action of lacidipine independent of its antihypertensive action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
150
1
21

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 460 publications
(175 citation statements)
references
References 24 publications
3
150
1
21
Order By: Relevance
“…Observational studies established a graded positive relation between BP levels and CVD risk,1, 2 and randomized controlled trials demonstrated that reductions in BP levels through antihypertensive treatment were paralleled by reductions in CVD events 3, 4. Ample evidence indicates that antihypertensive treatment also reduces the burden of subclinical CVD, including regression of left ventricular (LV) mass, carotid intima‐media thickness, and urinary albumin excretion, during short‐term follow‐up 5, 6, 7, 8. Most of the latter analyses, however, focused on selected parameters of subclinical disease and were performed in clinical trials with limited durations of follow‐up6, 8 or in clinical samples of modest size 5, 7…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observational studies established a graded positive relation between BP levels and CVD risk,1, 2 and randomized controlled trials demonstrated that reductions in BP levels through antihypertensive treatment were paralleled by reductions in CVD events 3, 4. Ample evidence indicates that antihypertensive treatment also reduces the burden of subclinical CVD, including regression of left ventricular (LV) mass, carotid intima‐media thickness, and urinary albumin excretion, during short‐term follow‐up 5, 6, 7, 8. Most of the latter analyses, however, focused on selected parameters of subclinical disease and were performed in clinical trials with limited durations of follow‐up6, 8 or in clinical samples of modest size 5, 7…”
Section: Introductionmentioning
confidence: 99%
“…Ample evidence indicates that antihypertensive treatment also reduces the burden of subclinical CVD, including regression of left ventricular (LV) mass, carotid intima‐media thickness, and urinary albumin excretion, during short‐term follow‐up 5, 6, 7, 8. Most of the latter analyses, however, focused on selected parameters of subclinical disease and were performed in clinical trials with limited durations of follow‐up6, 8 or in clinical samples of modest size 5, 7…”
Section: Introductionmentioning
confidence: 99%
“…1 The European Lacidipine Study on Atherosclerosis (ELSA) examined the effects of a 4-year treatment with lacidipine or atenolol in 2334 patients with hypertension, in whom blood pressure was measured at yearly intervals both by clinic and 24-h monitoring. 2,3 In the pre-randomization state there were marked differences between these two blood pressure values. Furthermore, and more importantly, the effect of treatment on clinic blood pressure was not accurately reflected by the effect of treatment on ambulatory blood pressure, the two sets of values showing a significant but very weak relationship throughout the study.…”
Section: Clinic Versus Ambulatory Blood Pressure Controlmentioning
confidence: 99%
“…Проте в інших подібних дослідженнях спосте-КЛІНІЧНІ ДОСЛІДЖЕННЯ / CLINICIAL RESEARCHES рігалося лише сповільнення збільшення величини ТКІМ на фоні певної терапії. Так, у дослідженні ELSA величина ТКІМ збільшувалася в обох групах, але у групі лацидипіну ТКІМ у кінці дослідження була достовірно меншою, ніж у групі атенололу [57]. Причому цей позитивний ефект антагоніста каль-цію не вплинув на прогноз -групи не відрізняли-ся за частотою виникнення несприятливих подій.…”
Section: клінічні дослідження / Clinicial Researchesunclassified